2017
DOI: 10.1021/acs.est.7b02786
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Urban Heat Island on Aerosol pH

Abstract: The urban heat island (UHI) is a widely observed phenomenon whereby urban environments have higher temperatures and different relative humidities than surrounding suburban and rural areas. Temperature (T) and relative humidity (RH) strongly affect the partitioning of semivolatile species found in the atmosphere, such as nitric acid, ammonia, and water. These species are inherently tied to aerosol pH, which is a key parameter driving some atmospheric chemical processes and environmental effects of aerosols. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 68 publications
13
53
0
Order By: Relevance
“…However, it is worth noting that particle acidity is not likely a factor in the relative split between reversible and irreversible aqSOA formed from isoprene. Studies predict that particles in the eastern USA are highly acidic throughout the year Battaglia et al, 2017;Guo et al, 2016Guo et al, , 2015, and acidity is not a limiting factor in isoprene SOA formation during the summer Xu et al, 2015). The implication from our observations is that reversible aqSOA from isoprene forms even in the presence of such persistently acidic particles.…”
Section: Atmospheric Implicationssupporting
confidence: 52%
“…However, it is worth noting that particle acidity is not likely a factor in the relative split between reversible and irreversible aqSOA formed from isoprene. Studies predict that particles in the eastern USA are highly acidic throughout the year Battaglia et al, 2017;Guo et al, 2016Guo et al, , 2015, and acidity is not a limiting factor in isoprene SOA formation during the summer Xu et al, 2015). The implication from our observations is that reversible aqSOA from isoprene forms even in the presence of such persistently acidic particles.…”
Section: Atmospheric Implicationssupporting
confidence: 52%
“…For systems where a single mixed aerosol phase is assumed, current work indicates dissociating organic acids do not strongly affect pH, and the limited studies to date suggest that inorganic species drive pH (Battaglia et al, 2019;Song et al, 2018;Vasilakos et al, 2018). For the southeastern US, pH changes predicted by E-AIM were generally limited to < 0.2 pH units in response to dramatic increases in oxalic acid .…”
Section: Role Of Organic-inorganic Interactionsmentioning
confidence: 80%
“…Although studies have confirmed that the liquid water content can be in agreement with observations and in combination with semivolatile partitioning measurements provide a well-constrained estimate for aerosol pH, the ALWC predictions central to the pH calculations are not routinely evaluated. While organics do not appreciably affect pH in particles consisting of a single aqueous phase (Battaglia Jr. et al, 2019), the presence of organic species could result in highly viscous (semisolid or glassy) particles where the system is not at equilibrium and pH has a heterogeneous distribution throughout the particle. All these factors eventually limit the precision and range of atmospheric conditions for which pH estimates based on semivolatile species partitioning can be used.…”
Section: Semivolatile Species Partitioningmentioning
confidence: 99%
See 1 more Smart Citation
“…pH is defined as the negative logarithm with base 10 of the hydrogen ion activity Battaglia et al, 2017):…”
Section: Ph Prediction By Thermodynamic Modelsmentioning
confidence: 99%